Soluble VEGF receptor 1 promotes endothelial injury in children and adolescents with lupus nephritis - Edelbauer-Wechselberger, Monika; Billing, Heiko; Tönshoff, Burkhard (Pediatric nephrology, 2012)
BackgroundEndothelial cell injury plays a key role in the pathogenesis of lupus nephritis (LN) and atherosclerosis. The aim of this study was to identify factors involved in the process of endothelial damage in children and adolescents with LN.MethodsWe evaluated the relationship between plasma vascular endothelial growth factor (VEGF), its soluble receptors sVEGFR-1 and sVEGFR-2 and markers of endothelial inflammation and injury (angiopoietin-2 and thrombomodulin, respectively) in 23 children and adolescents with LN (active LN, n = 14; inactive LN, n = 9; mean age 15 years) and 20 healthy controls (HC; mean age 12 years).ResultsVEGF, sVEGFR-1, angiopoietin-2 and thrombomodulin levels were significantly higher in children and adolescents with active LN than in patients in remission or HC. In active LN, however, VEGF was inversely related to sVEGFR-1 (r = −0.802, p < 0.001), angiopoietin-2 (r = −0.684, p = 0.007) and thrombomodulin (r = −0.697, p = 0.006). There was a significant positive correlation between sVEGFR-1 and thrombomodulin (r = 0.814, p < 0.0001), but sVEGFR-2 did not significantly differ between the patient groups and did not correlate with thrombomodulin (r = 0.046, p = 0.833).ConclusionssVEGFR-1 may play an important role in promoting endothelial damage in children and adolescents with active LN and could possibly be used to monitor disease severity.
First online: 07 December 2011
Gesehen am 18.04.2019